1981
DOI: 10.1136/thx.36.8.571
|View full text |Cite
|
Sign up to set email alerts
|

Induction of bronchial hypersensitivity: evidence for a role for prostaglandins.

Abstract: Bronchial hyper-responsiveness is a particular feature of asthma, but also occurs in normal subjects after a viral upper the second by saline as placebo. The study was performed double-blind and in random order. After pretreatment with PGF2ot the histamine dose-response curve was significantly shifted to the left in a parallel fashion (p < 0-001). There was a significant decrease in the doses of histamine required to cause a 20 fall in sGaw (p < 00015) but no significant change in the slopes of the dose-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In contrast, PGHS-derived eicosanoids have been reported to have both detrimental and beneficial effects in the airway, thus their role in the development of allergic lung disease is more complex. For example, PGD 2 , PGF 2α , and TxA 2 cause bronchoconstriction and are thought to be important in the development of airway hyperresponsiveness in animals and humans (8,9,(32)(33)(34). On the other hand, PGE 2 is a bronchodilator, blocks the early and late asthmatic responses to allergen challenge, and prevents the bronchoconstriction that accompanies nonsteroidal anti-inflammatory agent ingestion in aspirinsensitive asthmatics (9,13,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PGHS-derived eicosanoids have been reported to have both detrimental and beneficial effects in the airway, thus their role in the development of allergic lung disease is more complex. For example, PGD 2 , PGF 2α , and TxA 2 cause bronchoconstriction and are thought to be important in the development of airway hyperresponsiveness in animals and humans (8,9,(32)(33)(34). On the other hand, PGE 2 is a bronchodilator, blocks the early and late asthmatic responses to allergen challenge, and prevents the bronchoconstriction that accompanies nonsteroidal anti-inflammatory agent ingestion in aspirinsensitive asthmatics (9,13,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Four of this group proved to have lung cancer, always on the side opposite to the one that was lavaged. The study followed internationally agreed guidelines27 and all subjects fulfilled the following criteria: (1) age 16-75 years, with an FEV, over 60% of the predicted value; (2) no oral corticosteroids for at least the previous three months; (3) no evidence of a chest or upper respiratory tract infection within eight weeks.…”
Section: Subjectsmentioning
confidence: 99%
“…Several other investigations have suggested that inflammation is responsible for a change in the airways responsiveness, possibly due to the superficial location of irritant subepithelial receptors, and the associated bronchial inflammatory response that might occur after heavy irritant exposure. 46,47 Presently, the OSHA PEL for chlorine is 1 ppm as a ceiling limit. The NIOSH REL and ACGIH TLV for chlorine are 0.5 ppm as a TWA; however, the REL is based on a 10-hour workday while the TLV is based on an 8-hour workday.…”
Section: Chlorine and Pulmonary Toxicitymentioning
confidence: 99%